The ETIKA RELASIONALITAS ARMADA RIYANTO DAN RELEVANSINYA BAGI KESADARAN EKOLOGIS MASYARAKAT MANGGARAI - Hamat, Yulianus Evantus; Pandor, Pius (Jurnal Filsafat Indonesia, 2025)
The main focus of this article is to examine the philosophy of ethical relationality according to Armada Riyanto in fostering ecological awareness among the Manggarai community. The human environment and other creatures uphold the principle of unity that is mutually complementary, in which a harmonious and interdependent relationship is established, supporting each other's existence. However, within this harmonious relationship, a critical question arises: Is the principle that declares the ethics of unity and harmony between humans and other beings still relevant today? In reality, the natural habitat is currently plagued by very serious problems. This awareness prompts the author to elaborate on Armada Riyanto's philosophy of relationality in addressing ecological issues in Manggarai. Using a qualitative and phenomenological approach, this study highlights the relevance of ethical relationality in shaping the Manggarai people's awareness of their relationship with nature. The findings of this study reveal that Armada Riyanto’s philosophy of ethical relationality can serve as a foundation for the Manggarai community to develop a sense of responsibility toward nature. By understanding the relationality between humans and nature, it is hoped that the Manggarai community can possess and cultivate ecological awareness, which is increasingly manifested in concrete actions—particularly in how they perceive nature as a “brother” whose existence must be acknowledged and preserved.